Less than ideal victims: Understanding barriers to Queer men’s recognition of male-perpetrated intimate partner violence through Christie’s ‘Ideal Victim’ framework - McAulay, Joseph Patrick (International review of victimology, 2024)
Queer men who experience Intimate Partner Violence (IPV) from male romantic partners have long struggled to recognise that they are being abused or to identify themselves as victims. I argue that Nils Christie’s framework of the Ideal Victim can help us to understand the cultural and social dynamics which work to prevent these men from identifying their experiences as forms of victimisation. This paper uses data gathered from interviews with Queer male victims of male-perpetrated IPV to investigate this potential relationship, attempting to find out how the men understood their experiences of violence and abuse in relation to wider cultural norms and images of victimisation. This analysis reveals two key themes. First, within the men’s accounts, the images of the Ideal Victim and Offender are heavily gendered and because of this, the men struggled to relate their own experiences of victimisation to what they perceive to be the heavily feminised figure of the Ideal Victim. Second, within the men’s account, there was a ‘Public Story’ of IPV in which relationship abuse had to be physical, frequent, and all-consuming to be taken seriously. This ‘Public Story’ constrained the men’s ability to understand their partner’s actions as IPV and made them doubt the validity and legitimacy of their own experiences in which emotional manipulation and psychological abuse were often more frequent and devastating than physical assault. From these findings, I argue that there is an urgent need to confront the Public Story of IPV and its related Ideal Victim to craft more inclusive public narratives of relationship abuse in which Queer male victims can find legitimacy and support for their experiences.